1980
DOI: 10.1002/jcp.1041030114
|View full text |Cite
|
Sign up to set email alerts
|

Changes in RNA polymerase II in a cell cycle‐specific temperature‐sensitive mutant of hamster cells

Abstract: tsAF8 cells are a temperature-sensitive mutant of BHK cells that arrest at the nonpermissive temperature in the G1 phase of the cell cycle. The activity of solubilized RNA polymerase II and its ability to bine [3H]-gamma-amanitin decrease in tsAF8 cells at 40.6 degrees, with a half-life of approximately 10 hr. No appreciable changes occur in these two parameters in tsAF8 cells at 34 degrees or in BHK cells at either 34 degrees or 40.6 degrees. Protein synthesis is not appreciably affected for at least 24 hr af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
1

Year Published

1980
1980
1992
1992

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 28 publications
0
19
1
Order By: Relevance
“…To test accumulated levels of each RNA after stable DNA transfection, polyclonal cell lines were generated by transfection of each construct into mouse L cells or tsAF8 cells, a line of baby hamster kidney cells that contains a temperature-sensitive RNA polymerase II (Meiss and Basilico 1972;Rossini et al 1980; ]askulski and Baserga 1988). After selection for G418 resistance, >200 colonies were pooled for each construct.…”
Section: Reduced Accumulation Of Mrnas Containing the Gm-csf A U Domamentioning
confidence: 99%
See 1 more Smart Citation
“…To test accumulated levels of each RNA after stable DNA transfection, polyclonal cell lines were generated by transfection of each construct into mouse L cells or tsAF8 cells, a line of baby hamster kidney cells that contains a temperature-sensitive RNA polymerase II (Meiss and Basilico 1972;Rossini et al 1980; ]askulski and Baserga 1988). After selection for G418 resistance, >200 colonies were pooled for each construct.…”
Section: Reduced Accumulation Of Mrnas Containing the Gm-csf A U Domamentioning
confidence: 99%
“…The baby hamster kidney cell line tsAF8 (Rossini et al 1980; obtained from J. Corden, Johns Hopkins University School of Medicine, Baltimore, MD) was maintained at 34°C in Dulbecco's modified Eagle medium (DMEM) with 1 gram/liter of glucose and supplemented with 10% fetal calf serum and 10% COz. To obtain stable polyclonal lines, 18-24 hr before transfection, -106 cells were seeded per 100-mm culture dish.…”
Section: Cell Culture and Transformationsmentioning
confidence: 99%
“…The second hypothesis has been taken into account by a number of authors to explain the relationships between r RNA synthesis and cell cycle progression [4, 19, 201. However, it has been shown, at least for mammalian cells, that the inhibition of rRNA processing is not related to the beginning of the S phase [21, 221, while the possibility cannot be excluded that a continued nucleolar transcription activity is a prerequisite for DNA synthesis [22, 231. Instead, a clear correlation has been observed between mRNA synthesis and the G1/S transition [24,25]. Specific gene products are required at this point of the cell cycle, and mutants that have a temperature-sensitive RNA polymerase activity, such as TSAF8 [24], or cells treated with inhibitors that specifically inhibit mRNA synthesis are not able to progress towards DNA synthesis and remain in G, phase [25].…”
Section: Ribosomal R N a Synthesis And Processingmentioning
confidence: 99%
“…The CHO cell lines are notoriously poor recipients for DNA transformation, but it is not immediately apparent why transfer to the quite competent Ltk-cell line was unsuccessful. One explanation may be that a-amanitin too rapidly inactivates RNA polymerase II activity, whereas the half-life of polymerase II of the TS mutant TsAF8 when shifted to 40°C is at least 12 to 15 h and the cells remain viable at nonpermissive temperatures for as long as 40 h (20,21). Retention of some recipient cell RNA polymerase II activity during the early stages of selection of transformants may be essential.…”
mentioning
confidence: 99%
“…Previous studies of this mutant suggested that its RNA polymerase II could be the function which has the TS mutation. Growth at 40°C results in a selective loss of the activity of RNA polymerase II (20) and a loss of polymerase II molecules as quantitated by [3H]amanitin binding (21). More importantly, this TS mutation in TsAF8 was complemented by fusion with wild-type CHO cells, but not by fusion with the CHO cell TS polymerase II mutant TsAmaR-1 (22).…”
mentioning
confidence: 99%